2021
DOI: 10.26529/cepsj.1150
|View full text |Cite
|
Sign up to set email alerts
|

Lost Trust? The Experiences of Teachers and Students during Schooling Disrupted by the Covid-19 Pandemic

Abstract: This paper aims to help understand how relational trust between students and teachers embedded in the teaching-learning process unfolded during the emergency distance and flexible hybrid education in Serbia in 2020. It also identifies niches in student-teacher relationships that hold potential for repairing and building trust. For the student-teacher relationship to be trust-based and thus conducive to students’ learning and wellbeing, a consensus about role expectations must be achieved. As the Covid-19 crisi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Moreover, school closure decreased the motivation for work among both teachers and pupils (Kustec et al, 2020; and increased problems in providing adequate equipment for individual pupils (Šef, 2020), as well as specialised teaching equipment and specialised classrooms for schools (ZASSS, 2020). Similar observations were made in various countries, namely a lack of IT devices, insufficient IT skills of students and teachers (Nedzinskaite-Maciuniene et al, 2022), a lack of children's interest in learning (Drvodelić & Domović, 2022), difficulties with following students' development especially in the area of assessment and evaluation (Özgür Karataş, et al, 2021), and heavy workload and poor performance of teachers (Zorkić, et al, 2021).…”
Section: Introductionsupporting
confidence: 66%
“…Moreover, school closure decreased the motivation for work among both teachers and pupils (Kustec et al, 2020; and increased problems in providing adequate equipment for individual pupils (Šef, 2020), as well as specialised teaching equipment and specialised classrooms for schools (ZASSS, 2020). Similar observations were made in various countries, namely a lack of IT devices, insufficient IT skills of students and teachers (Nedzinskaite-Maciuniene et al, 2022), a lack of children's interest in learning (Drvodelić & Domović, 2022), difficulties with following students' development especially in the area of assessment and evaluation (Özgür Karataş, et al, 2021), and heavy workload and poor performance of teachers (Zorkić, et al, 2021).…”
Section: Introductionsupporting
confidence: 66%
“…Although the promotion of a positive classroom climate is often viewed as the responsibility of the classroom teacher, examining and including students' perspectives and ideas is vital. This is illustrated in the work by Zorkić et al (2021), where teacher and student views offer interesting parallels, and Smith (2013) who found contradictions between students' and teachers' responses. Students' perspectives on student-teacher relationships in face-to-face learning environments has provided useful insights for educators (García-Moya et al, 2020), and should especially be considered in online and technologyenhanced learning environments due to their advanced experience with technology.…”
Section: Students' Voices and Diversitymentioning
confidence: 99%
“…Analysing the narratives of students and teachers, Zorkić et al (2021) found disruptions of trust between them. For instance, students reported disruptions in respect, noting teachers expressed anger, lack of patience, or increasing demands.…”
Section: Experiences During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…While support systems are welcome, our experience is that there are often tensions between the institutional expectations for reporting and record keeping and the need to build trust and relationships between those tasked with student support and the students they support [5,6]. For example, institutional protocols on documentation can create a sense of surveillance [5].…”
Section: Introductionmentioning
confidence: 99%